Anesthesiology mentoring. Issue 6 (December 2016) - Wenzel, Volker; Gravenstein, Nikolaus
Abstract : Purpose of review: Mentoring is fundamentally valuable and important to students considering a path into our specialty, as well as to colleagues already in it and with ambition to advance. General principles and personal experiences are collected and described to help inform future mentors and to reinforce the value of having a mentor and the satisfaction (and work) that is associated with such a role. Recent findings: Detecting a latent talent among medical students or residents may be challenging but is worth the effort to develop personal careers and the specialty itself. Upon agreeing to jointly move a certain project, a professional plan is needed to improve chances of success and decrease the likelihood of frustration. Various challenges always have to be detected and solved, with the ultimate goal to guide a medical student to residency, subsequently into faculty status and preferably to lifelong collaboration. Summary: Access to a mentor is an often-cited key to choosing a specialty and the success of junior colleagues and thus the entire department. Mentoring is fundamentally valuable in providing role modeling and also in protecting the mentee from the inefficiency of learning lessons the hard way.